The Effect of Good Corporate Governance on Corporate Social Responsibility in Real Estate Companies Listed on the Indonesia Stock Exchange - Maya Sari; Try Utami Kesuma Wardani (Journal of International Conference Proceedings (JICP), 2021)
The goal of this research was to see how the composition of a good corporate governance board affects the independent board of commissioners, managerial ownership, institutional ownership, and partially audit committee's disclosure of corporate social responsibility, as well as how good corporate governance affects disclosure of corporate social responsibility in real estate companies. Listed on the Indonesian Stock Exchange. The population used in this study were all Real Estate companies listed on the Indonesia Stock Exchange (BEI) in 2015-2019 and samples from research on Real Estate companies were 9 companies with 5 years of observation. The documentation method was utilized to collect data for this study. In this study, descriptive statistics, multiple linear regression analysis, partial test, and determinant test were employed as analysis methods. The findings reveal that while independent commissioners, managerial ownership, and the audit committee have no impact on corporate social responsibility, institutional ownership does. and independent commissioners, management ownership, institutional ownership, and the audit committee all have a substantial impact on corporate governance. Real Estate Companies Listed on the Indonesian Stock Exchange Have a Social Responsibility.